2013
DOI: 10.1111/jne.12082
|View full text |Cite
|
Sign up to set email alerts
|

Endocannabinoid Receptor Deficiency Affects Maternal Care and Alters the Dam's Hippocampal Oxytocin Receptor and Brain‐Derived Neurotrophic Factor Expression

Abstract: Maternal care is the newborn's first experience of social interaction, and this influences infant survival, development and social competences throughout life. We recently found that postpartum blocking of the endocannabinoid receptor-1 (CB1R) altered maternal behaviour. In the present study, maternal care was assessed by the time taken to retrieve pups, pups' ultrasonic vocalisations (USVs) and pup body weight, comparing CB1R deleted (CB1R KO) versus wild-type (WT) mice. After culling on postpartum day 8, hip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 83 publications
(93 reference statements)
3
17
0
Order By: Relevance
“…This hypothesis is supported by the normal behavior of Dagla 2/2 mice in the social preference test, which indicates that the altered maternal behavior is not due to a generally impaired social interest of the knockout animals. Our hypothesis is also in line with previous studies showing that treatment with rimonabant or deletion of the CB 1 resulted in slower pup retrieval (30,31), whereas nursing was not affected. The authors of this study (31) have also suggested that the increased stress sensitivity of CB1 2/2 mice (24,25) contributed to the deficit in maternal care.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This hypothesis is supported by the normal behavior of Dagla 2/2 mice in the social preference test, which indicates that the altered maternal behavior is not due to a generally impaired social interest of the knockout animals. Our hypothesis is also in line with previous studies showing that treatment with rimonabant or deletion of the CB 1 resulted in slower pup retrieval (30,31), whereas nursing was not affected. The authors of this study (31) have also suggested that the increased stress sensitivity of CB1 2/2 mice (24,25) contributed to the deficit in maternal care.…”
Section: Discussionsupporting
confidence: 92%
“…Our hypothesis is also in line with previous studies showing that treatment with rimonabant or deletion of the CB 1 resulted in slower pup retrieval (30,31), whereas nursing was not affected. The authors of this study (31) have also suggested that the increased stress sensitivity of CB1 2/2 mice (24,25) contributed to the deficit in maternal care. Nevertheless, we Anxiety, Stress and Fear Response in Dagla 2/2 Mice cannot rule out the possibility that a dysfunctional maternal behavior contributed to the anxiety-, fear-, and stress-related behavioral phenotypes.…”
Section: Discussionsupporting
confidence: 92%
“…Parturition and maternal care are pivotal social events eliciting hormonal responses, including elevated release of Oxytocin, which is strongly implicated in social interactions 25 . Furthermore, studies demonstrated that dams display elevated defensive behavior postpartum 26 27 .…”
Section: Resultsmentioning
confidence: 99%
“…Protein was extracted from placentae and analyzed as previously (Nesher et al, 2015;Schechter et al, 2013), with modifications. Whole frozen placentae were immersed in chilled (4 C) radioimmunoprecipitation assay (RIPA) buffer comprised of 1% Triton X-100, 0.5% sodium deoxycholate, 0.1% sodium dodecyl sulfate and 150 mM sodium chloride in 50 nM tris(hydroxymethyl)aminomethane (pH 8), to which protease inhibitor cocktail (04693159001 Roche, Hod Hasharon, Israel) was added 1:25 to the RIPA buffer, as well as 1 mM sodium orthovanadate, 5 mM ethylenediaminetetraacetic acid (EDTA) and 5 mM sodium fluoride, immediately prior to use.…”
Section: Western Blot Analysismentioning
confidence: 99%